Mechanistic Observation of Interactions between Macrophages and Inorganic Particles with Different Densities. Issue 4 (29th November 2022) - Zhang, Chengchen; Tang, Jianbo; Xie, Wanjie; Allioux, Francois‐Marie; Cao, Zhenbang; Biazik, Joanna M.; Tajik, Mohammad; Deng, Fei; Li, Yi; Abbasi, Roozbeh; Baharfar, Mahroo; Mousavi, Maedehsadat; et al.
Abstract: Many different types of inorganic materials are processed into nano/microparticles for medical utilization. The impact of selected key characteristics of these particles, including size, shape, and surface chemistries, on biological systems, is frequently studied in clinical contexts. However, one of the most important basic characteristics of these particles, their density, is yet to be investigated. When the particles are designed for drug delivery, highly mobile macrophages are the major participants in cellular levels that process them in vivo. As such, it is essential to understand the impact of particles' densities on the mobility of macrophages. Here, inorganic particles with different densities are applied, and their interactions with macrophages studied. A set of these particles are incubated with the macrophages and the outcomes are explored by optical microscopy. This microscopic view provides the understanding of the mechanistic interactions between particles of different densities and macrophages to conclude that the particles' density can affect the migratory behaviors of macrophages: the higher the density of particles engulfed inside the macrophages, the less mobile the macrophages become. This work is a strong reminder that the density of particles cannot be neglected when they are designed to be utilized in biological applications. Abstract : This work provides a study for understanding the mechanistic interactions between particles of different densities and the mobility of macrophages to conclude that the particles' densities can affect the migratory behaviors of macrophages: the higher the density of particles engulfed inside the macrophages, the less mobile the macrophages become.